THE EFFECT OF PROMOTION AND QUALITY OF SERVICE ON MOTORCYCLE CONSUMER SATISFACTION (CASE STUDY OF STIE INDRAGIRI) - Hermanto Hermanto; Walmi Sholihat; Astarman Astarman (LPPM Press STIE Indragiri Rengat, 2021)
This research was conducted at the Indragiri Rengat School of Economics, especially students who use motorbikes. The purpose of this study was to determine the effect of promotion and service quality on motorcycle consumer satisfaction (case study of STIE Indragiri students). With the number of samples used as many as 94 respondents. Data processing using the IBM SPSS Statistic 21 program. The results of the study can be concluded that: (1) Promotion partially affects motorcycle consumer satisfaction (case study of STIE Indragiri students). (2) Service quality partially affects motorcycle consumer satisfaction (case study of STIE Indragiri students). (3) Promotion and service quality simultaneously affect motorcycle consumer satisfaction (case study of STIE Indragiri students). The influence of the Promotion and Service Quality variables on the consumer satisfaction variable is very strong, with a contribution of 86%, while the other variables not examined are 14%.